Geochemical Modeling of Water-Rock Interaction in the Granulite Rocks of Lower Crust in the Serre Massif (Southern Calabria, Italy) - Carmine Apollaro (Geofluids)
To simulate the evolution of groundwaters interacting with granulitic rocks of the lower crust exposed in the southern sector of the Calabrian region, reaction path modeling was performed by means of the EQ3/6 software package version 8.0a. Low-salinity waters issuing from granulite have Na–Cl to Na-HCO3 composition, about neutral pH (mean value of 6.7), outlet temperatures of 7.7 to 14.2°C, oxidant redox potentials from 100 to 182 mV, and electrical conductivity from 72.1 to 196.9 μS/cm. The mineral constituents of local granulite are plagioclase, amphibole, biotite, clinopyroxene, garnet, and orthopyroxene. Simulations were carried at constant temperature of 11.8°C (which reproduces the average temperature of local groundwaters) fixing the fugacity of CO2 at 10-2.4 bar (mean value), 10-2.0 bar (mean value +1 σ), and 10-2.8 bar (mean value -1 σ). The analytical contents of major elements in groundwaters were satisfactorily reproduced by modeling and are fully consistent with the secondary minerals produced by weathering processes affecting the same rocks.